Makna Diksi Pada Lagu “Kucari Kamu” Payung Teduh - Muhamad Iqbal Majdy; Muhammad Ikmal A (Simpati, 2023)
The song "Kucari Kamu" is one of the works of the music group Payung Teduh which has beautiful lyrics but takes a long time to understand the diction. This song raises many interpretations, especially in the I-you point of view in the lyrics. Therefore, this song will be very interesting to research. The objectives of this research are (1) to know the I-you point of view in the lyrics, (2) to interpret the lyrics. This research is based on our love for Payung Teduh songs and curiosity about the meaning of the lyrics of this song created by Moh. Istiqamah Djamad. The research method we will use is qualitative research method. The results of this research are understanding the meaning of the lyrics of the song "Kucari Kamu" and knowing the I-you point of view in the lyrics of the song "Kucari Kamu" based on people's perceptions.